(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Planonth S, Chantarasiri A. 2022. The oleaginous yeast Pichia manshurica isolated from Lansium domesticum fruit in Thailand and its fatty acid composition of single cell oil. Biodiversitas 23: 801-809. Oleaginous microbes can accumulate intracellular lipids or single cell oils (SCOs) in quantities higher than 20% of their biomass. They can be a sustainable alternative to fossil fuels, biofuels, and oleochemicals. Studies concerning efficient oleaginous yeasts isolated from the natural environments remain scarce. Therefore, this study isolated and screened for efficient oleaginous yeasts from the surfaces of longkong fruit (Lansium domesticum) samples in Thailand. Their intracellular SCOs were extracted using an ultrasonic-assisted extraction (UAE) method and quantitatively analyzed. The SCO-accumulating yeasts (produce the amount of SCOs <20 % of their biomass) genetically identified were Candida jaroonii, Meyerozyma caribbica, Kodamaea ohmeri, and Pichia sp., while the oleaginous yeasts (produce the amount of SCOs >20% of their biomass) identified were Pichia manshurica and Hanseniaspora opuntiae. Several isolated yeasts were designated as rare oleaginous microbes. The P. manshurica strain Y2 was considered as the most effective oleaginous yeast with a SCO content of 43.03% (w/w). The fatty acids in the accumulated SCO of this strain were analyzed by gas chromatography (GC) that consisted of palmitic, stearic, oleic, linoleic, and palmitoleic acids. These fatty acids could be further applied in the production of third-generation biodiesel, cocoa butter equivalents, and related high-value oleochemicals.